2018
DOI: 10.7150/jca.22378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weight Loss at Presentation on Survival in Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitors (EGFR-TKI) Sensitive Mutant Advanced Non-small Cell Lung Cancer (NSCLC) Treated with First-line EGFR-TKI

Abstract: Purpose The aim of this study is to evaluate the impact of weight loss at presentation on treatment outcomes of first-line EGFR-tyrosine kinase inhibitors (EGFR-TKI) in EGFR-TKI sensitive mutant NSCLC patients.Methods We retrospectively analyzed the clinical outcomes of 75 consecutive advanced NSCLC patients with EGFR-TKI sensitive mutations (exon 19 deletion or exon 21 L858R) received first-line gefitinib or erlotinib therapy according to weight loss status at presentation in our single center.Results Of 75 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In recent research [32], weight loss during definitive radiotherapy was observed to result in a worse OS rate in patients with locally advanced NSCLC. Previous research found that a weight reduction at presentation had a negative influence on the survival outcomes in patients with EGFR-mutant advanced NSCLC that was treated with first-line EGFR-TKI [33]. Weight loss, independent of EGFR mutation status, was linked with a poor outcome in our research.…”
Section: Discussionsupporting
confidence: 53%
“…In recent research [32], weight loss during definitive radiotherapy was observed to result in a worse OS rate in patients with locally advanced NSCLC. Previous research found that a weight reduction at presentation had a negative influence on the survival outcomes in patients with EGFR-mutant advanced NSCLC that was treated with first-line EGFR-TKI [33]. Weight loss, independent of EGFR mutation status, was linked with a poor outcome in our research.…”
Section: Discussionsupporting
confidence: 53%
“…Gefitinib, an EGFR-TKI, is the first targeted drug to treat advanced-stage NSCLC. [38][39][40] Our data showed that gefitinib reduces cell viability and proliferation in PC9 cells. Angiogenesis was also inhibited by gefitinib.…”
Section: Discussionmentioning
confidence: 89%
“…Several retrospective studies reported that BMI and weight loss were associated with survival in patients with solid tumors who received TKI therapies. [21][22][23][24] However, changes in body weight may be masked by weight gain in ascites, peripheral edema, and growth of primary and metastatic tumors. 25,26 Therefore, in addition to sustained weight loss >5% or weight loss >2% with BMI <20 kg/m 2 , sarcopenia was also taken into consideration in the international consensus for cachexia diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is a severe problem affecting prognosis and quality of life in patients receiving anticancer therapy. Several retrospective studies reported that BMI and weight loss were associated with survival in patients with solid tumors who received TKI therapies 21–24 . However, changes in body weight may be masked by weight gain in ascites, peripheral edema, and growth of primary and metastatic tumors 25,26 .…”
Section: Discussionmentioning
confidence: 99%